MÚLTIPLOS CENÁRIOS DA EDUCAÇÃO DE JOVENS E ADULTOS EM MATO GROSSO DO SUL A PARTIR DE NARRATIVAS DE PROFESSORES DE MATEMÁTICA. - LILIAN OLIVEIRA DANIEL (2022)
What can Youth and Adult Education in Mato Grosso do Sul do? In this work, we produce a history of the Education of Youths and Adults of Mato Grosso do Sul, from the point of view of the Mathematics teachers of the modality. With this research question, we investigated scenarios of 12 EJA schools in the state and talked with 12 teachers from 12 different municipalities. We seek to highlight the particularities, the challenges, the reality, the daily life of the EJA school. Our research has been based on the production of narratives using Oral History as a methodology. A democratic methodology that motivates the dialogue and collaboration of the subjects, valuing the experiences, memories, identities and subjectivities. We produced interviews with Mathematics teachers who taught at EJA in 2020. The teachers' narratives directed our gaze to how this very own school operates, to its mode of organization, to what can also happen in between, subverting some rules proposed by the norms, performing strategies and tactics mobilized by teachers in their daily professional activities. Teachers told us about intergenerational relationships, time at school, the youthfulness of students in the modality, Mathematics classes, Exclusion Processes, knowledge from experiences and the relationship between the offer of EJA courses and Exams. of Certification. When looking at the narratives, we noticed that the school is constituted through singularities determined by economic, social and cultural characteristics of each region, producing so many EJAs in different places in the state. We understand that the discussions did not end with this research, that many questions were suspended and that we still need to keep asking: what can other stories of Youth and Adult Education in Mato Grosso do Sul do?